Region-Specific Genetic Alterations in the Aging Hippocampus: Implications for Cognitive Aging - Burger, Corinna (Frontiers in Aging Neuroscience, 2010)
Aging is associated with cognitive decline in both humans and animals and of all brain regions, the hippocampus appears to be particularly vulnerable to senescence. Age-related spatial learning deficits result from alterations in hippocampal connectivity and plasticity. These changes are differentially expressed in each of the hippocampal fields known as cornu ammonis 1 (CA1), cornu ammonis 3 (CA3), and the dentate gyrus. Each sub-region displays varying degrees of susceptibility to aging. For example, the CA1 region is particularly susceptible in Alzheimer’s disease while the CA3 region shows vulnerability to stress and glucocorticoids. Further, in animals, aging is the main factor associated with the decline in adult neurogenesis in the dentate gyrus. This review discusses the relationship between region-specific hippocampal connectivity, morphology, and gene expression alterations and the cognitive deficits associated with senescence. In particular, data are reviewed that illustrate how the molecular changes observed in the CA1, CA3, and dentate regions are associated with age-related learning deficits. This topic is of importance because increased understanding of how gene expression patterns reflect individual differences in cognitive performance is critical to the process of identifying new and clinically-useful biomarkers for cognitive aging.